If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 4x + -1 = 12 Reorder the terms: 7 + -1 + 4x = 12 Combine like terms: 7 + -1 = 6 6 + 4x = 12 Solving 6 + 4x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4x = 12 + -6 Combine like terms: 6 + -6 = 0 0 + 4x = 12 + -6 4x = 12 + -6 Combine like terms: 12 + -6 = 6 4x = 6 Divide each side by '4'. x = 1.5 Simplifying x = 1.5
| 3(2x-1)-6x=-4 | | 8(n-2)-3(n-4)=6(n-7)+8 | | 3x-7=3x+13 | | -6(4x-2)=-24x+12 | | 1/4(4q+12)=2+18-3q | | 0.25+4.75=6 | | -12+21=-3 | | 18x+9y=360 | | 4x-11=-23 | | 3(2x-4)=21 | | 2x-4+0.5(2+8x)=0 | | 36-11=5(x-4) | | 33+3y-12=12y-9-4y | | -1y-22-1y=-16 | | 15=-3(n-4) | | x^2+26x+112=0 | | x+20+4x=-33-4x-37 | | 6x-6=10x+15-15 | | 5-(3)= | | 48f+6.4=-8.48 | | 10y+9=-3 | | 2(-2x+4)=8 | | -4(2x-3)-3-8x=-11 | | 24-6k=6[4-k] | | 10+45u= | | a+140=a+0.05a | | 15-6x+7-3x= | | -16+6=-6r+2 | | 10x-3y=24 | | 2(5+3)= | | 4x+28=6x+2 | | x^2+14x-18=10x+3 |